2021
DOI: 10.1021/acs.jafc.1c03485
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Multiple Biofunctions of Maca on Its Anti-allergic, Anti-inflammatory, Anti-thrombotic, and Pro-angiogenic Activities

Abstract: Four active partition layers and ten isolates, including (5R)-and (5S)-macapyrrolidone A (1a, 1b), and four new alkaloids, (5R)-and (5S)-macapyrrolidone B (2a, 2b) and macapyrrolins D, E (3, 4), were isolated from maca (Lepidium meyenii Walp.), an indigenous food plant from Peru. Derived from the n-hexane layer, the macamide-rich fraction exhibited pro-angiogenic activity on EPC and HUVEC cells. Anti-thrombotic activity was displayed by the polar part of maca extracts (n-butanol and water layers). Both 75% met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 39 publications
3
14
0
Order By: Relevance
“…By analyzing the 1 H and 13 C NMR spectra of compounds 4-7, it was determined that these molecules belonged to the capnellane-type sesquiterpenoids. The identification was made based on the spectroscopic data and a comparison with the literature references.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…By analyzing the 1 H and 13 C NMR spectra of compounds 4-7, it was determined that these molecules belonged to the capnellane-type sesquiterpenoids. The identification was made based on the spectroscopic data and a comparison with the literature references.…”
Section: Resultsmentioning
confidence: 99%
“…The IR spectrum exhibited absorption bands indicative of hydroxy (3548 cm −1 ) groups. Analysis of the 13 C NMR, DEPT, and HMQC spectra revealed that compound 3 consisted of 15 carbons (Table 4), including three methyls, three sp 3 methylenes, one sp 2 methylene, four sp 3 methines (including two oxymethines), three sp 3 quaternary carbons (including an oxygenated quaternary carbon), and one quaternary sp 2 carbon. The 1 H NMR spectrum displayed signals corresponding to three singlet methyls, five aliphatic methylenes, and two methines (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological activity of N-heterocyclic derivatives, such as antihistaminic, antimalarial, antiviral, antiparasitic, and anticancer activity, has been well established during the past few years. [22][23][24][25] The study on N-heterocycle containing drugs consequently becomes an attractive field in chemistry owing to their vast medicinal value. Based on the efficacy of clinically approved N-heterocyclic derivatives of lansoprazole, omeprazole, and albendazole, research focusing on the medicinal use of such compounds as potent anticancer chemotherapeutic agents remains desirable.…”
mentioning
confidence: 99%